Love people, use things : because the opposite never works - Millburn, Joshua Fields; Nicodemus, Ryan (Celadon Books, 2021)
"AS SEEN ON THE NETFLIX DOCUMENTARIES MINIMALISM & LESS IS NOW. How might your life be better with less? Imagine a life with less: less stuff, less clutter, less stress and debt and discontent-a life with fewer distractions. Now, imagine a life with more: more time, more meaningful relationships, more growth and contribution and contentment-a life of passion, unencumbered by the trappings of the chaotic world around you. What you're imagining is an intentional life. And to get there, you'll have to let go of some clutter that's in the way. In Love People, Use Things, Joshua Fields Millburn and Ryan Nicodemus move past simple decluttering to show how minimalism makes room to reevaluate and heal the seven essential relationships in our lives: stuff, truth, self, money, values, creativity, and people. They use their own experiences-and those of the people they have met along the minimalist journey-to provide a template for how to live a fuller, more meaningful life. Because once you have less, you can make room for the right kind of more"--